Complete Question:
Emily and Zach have two different polynomials to multiply: Polynomial product A: (4x2 – 4x)(x2 – 4) Polynomial product B: (x2 + x – 2)(4x2 – 8x) They are trying to determine if the products of the two polynomials are the same. But they disagree about how to solve this problem.
Answer:
![A = B](https://tex.z-dn.net/?f=A%20%3D%20B)
Step-by-step explanation:
<em>See comment for complete question</em>
Given
![A: (4x^2 - 4x)(x^2 - 4)](https://tex.z-dn.net/?f=A%3A%20%284x%5E2%20-%204x%29%28x%5E2%20-%204%29)
![B: (x^2 + x - 2)(4x^2 - 8x)](https://tex.z-dn.net/?f=B%3A%20%28x%5E2%20%2B%20x%20-%202%29%284x%5E2%20-%208x%29)
Required
Determine how they can show if the products are the same or not
To do this, we simply factorize each polynomial
For, Polynomial A: We have:
![A: (4x^2 - 4x)(x^2 - 4)](https://tex.z-dn.net/?f=A%3A%20%284x%5E2%20-%204x%29%28x%5E2%20-%204%29)
Factor out 4x
![A: 4x(x - 1)(x^2 - 4)](https://tex.z-dn.net/?f=A%3A%204x%28x%20-%201%29%28x%5E2%20-%204%29)
Apply difference of two squares on x^2 - 4
![A: 4x(x - 1)(x - 2)(x+2)](https://tex.z-dn.net/?f=A%3A%204x%28x%20-%201%29%28x%20-%202%29%28x%2B2%29)
For, Polynomial B: We have:
![B: (x^2 + x - 2)(4x^2 - 8x)](https://tex.z-dn.net/?f=B%3A%20%28x%5E2%20%2B%20x%20-%202%29%284x%5E2%20-%208x%29)
Expand x^2 + x - 2
![B:(x^2 + 2x - x - 2)(4x^2- 8x)](https://tex.z-dn.net/?f=B%3A%28x%5E2%20%2B%202x%20-%20x%20-%202%29%284x%5E2-%208x%29)
Factorize:
![B:(x(x + 2) -1(x + 2))(4x^2- 8x)](https://tex.z-dn.net/?f=B%3A%28x%28x%20%2B%202%29%20-1%28x%20%2B%202%29%29%284x%5E2-%208x%29)
Factor out x + 2
![B:(x -1) (x + 2)(4x^2- 8x)](https://tex.z-dn.net/?f=B%3A%28x%20-1%29%20%28x%20%2B%202%29%284x%5E2-%208x%29)
Factor out 4x
![B:(x -1) (x + 2)4x(x- 2)](https://tex.z-dn.net/?f=B%3A%28x%20-1%29%20%28x%20%2B%202%294x%28x-%202%29)
Rearrange
![B: 4x(x - 1)(x - 2)(x+2)](https://tex.z-dn.net/?f=B%3A%204x%28x%20-%201%29%28x%20-%202%29%28x%2B2%29)
The simplified expressions are:
and
![B: 4x(x - 1)(x - 2)(x+2)](https://tex.z-dn.net/?f=B%3A%204x%28x%20-%201%29%28x%20-%202%29%28x%2B2%29)
Hence, both polynomials are equal
![A = B](https://tex.z-dn.net/?f=A%20%3D%20B)